(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): Aim of the study was to explore the outcome of conservative treatment for the postmenopausal women having small cysts. Materials Methods: This prospective cross sectional study was carried out in ZH Sikder Women Medical College & Hospital, Medinova and Popular hospital between January 2011 to June 2016. Five hundred (500) postmenopausal women with simple cysts were enrolled after counseling and taking written consent. Inclusion criteria were- cysts size should not be more than 5cm, they should be unilocular, without having any solid component or any debries. Exclusion criteria were, she or her family should not have any cancer of ovary, breast, or colon. Also women with HRT were excluded from the study. Thorough history taking, clinical examination, and some investigation like CA125, and TVS with colour Doppler was carried out for all women. CT Scan. MRI, and PET Scan were reserved for cases where colour Doppler ultrasonogram was suspicious. All the patients were followed up every 3 months for 3 to 5 years. Surgery was done if the patient developed any symptoms, or if there was any increment of sizes of cysts or there was any sonographic changes were evident. MRI1 (malignancy risk index) was calculated for each patient. Data were analyzed by SPSS where all calculation rate of less than 0.05 was considered significant. Results: Among 500 cysts, 285 cysts resolved spontaneously, which is highly significant (p <0.05), 165 cysts needed surgery and 50 cysts regressed very slowly and did not regress completely. Histopathology of surgical specimen revealed all were benign except 4 cysts, which became malignant or malignant potential. Conclusion: Postmenopausal women with simple cysts not more than 5cm,which are unilocular, unilateral, without having any solid component and with normal Doppler study are rarely malignant. So if MRI 1 is below 200 we may avoid unnecessary surgery and assure the postmenopausal women for the conservative treatment with regular follow up. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 3-9